KAJIAN IDEOLOGI KARYA SASTRA FEMINISME TOKOH PEREMPUAN DALAM NOVEL “CINTA 2 KODI” KARYA ASMA NADIA - Nadha Nuur Annisa Suhendra; Miftahulkhairah Anwar; Evi Susanti (IKIP Siliwangi, 2023)
Examining feminist literary works is examining, understanding and analyzing literary works through feeling and thinking as connoisseurs of literary arts, which are of the female genre with multi-faceted problems that occur in society. An objective societal perspective on the position of women based on the lens of the millennial era. The purpose of this research is to analyze the female character in the novel